Aplikasi Manajemen Aset Dengan Penyusutan Menggunakan Metode Straight Line Pada Tv Kepri Tanjungpinang - Dwi Nurul Huda; Nurul Saepul; Saiful Najib (Jurnal Bangkit Indonesia, 2018)
Kepri TV is an agency engaged in television and audio-visual broadcasting. In this case, Kepri TV has many assets. Asset Management at Kepri TV is still not owned, so that asset data collection, borrowing and depreciation reporting are still done manually. This can be anticipated by using applications and calculating depreciation of assets using the Straight Line Method. Therefore we need an information system that can assist in the management of company assets. This application can assist in asset management, annual asset reporting, asset value monitoring, more recorded asset management data collection and managed and controlled asset borrowing and depreciation.